Humanização do nascimento em Porto Alegre: narrativa de práticas obstétricas - Davide Carbonai; Ricardo Herbert Jones (Cahiers des Amériques Latines)
The birth attendance system, its merchandising, and the enhanced medicalization, turned the experience of childbirth in Brazil into an eminently hospital event. By means of the narrative of Ricardo (gynecologist, obstetrician and activist of the humanizing movement of childbirth in Porto Alegre), the article explores the humanizing birth movement in Porto Alegre, the difficulties encountered in the implementation of humanized obstetric practices, the resistance of the hospital system and medical professionals.